Toxicity of traditionally dried processed Holothuria extract by fisherman in Kakara Islands, North Halmahera, Indonesia - Febrina Olivia Akerina (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2020)
Empirically, sea cucumber as a food ingredient that is believed to have efficacy as medicine (nutraceutical) because it contains bioactive compounds like terpenoid, saponin, essential amino acids, glycosaminglycan, chondroitin sulfate, sulfate polysaccharides, lectins, phenol and peptides. The aim of this research were to identify processing method performed by fisherman in Kakara Pulau and to determine the toxicity of dried sea cucumber extract againts Artemia salina larvae with three different solvents. The result showed that there were 8 types of sea cucumber that were dominant caught ny fisherman namely Kongkong, Joko, Susu, Kalengkong, Nanas, Benang, Badara dan Pasir. Most of them, process sea cucumber using a combination of smoking and drying. Based on the toxicity test, dried sea cucumber extract is included in the toxic category, which has the potential to be developed as an antibacterial.